Christmas in Germany : A Cultural History - Perry, Joe (Book collections on Project MUSE., 2010)
For poets, priests, and politicians--and especially ordinary Germans--in the nineteenth and twentieth centuries, the image of the loving nuclear family gathered around the Christmas tree symbolized the unity of the nation at large. German Christmas was supposedly organic, a product of the winter solstice rituals of pagan ""Teutonic"" tribes, the celebration of the birth of Jesus, and the age-old customs that defined German character. Yet, as Joe Perry argues, Germans also used these annual celebrations to contest the deepest values that held the German community together: faith, family, and lo.